Accounting choice in measurement and comparability: an examination of the effect of the fair value option - Fontes, Joana C.; Panaretou, Argyro; Shakespeare, Catherine (Review of Accounting Studies, 2025)
The choice between historical cost and fair value measurement is one of the most debated issues among accounting academics and practitioners. We use the election of the fair value option (FVO) to study the effects of entities’ measurement choices on accounting comparability. The FVO enables entities to use different measurement bases for similar assets and liabilities, raising questions about whether the FVO compromises or enhances comparability. Using a sample of US banks, we find that FVO elections increase comparability both across FVO electing banks and between FVO electing banks and banks that never elect the FVO but only if the FVO elections comply with the intent of the standard setters to remedy accounting mismatches. Overall our results suggest that banks elect the FVO to better present their economics, yielding higher comparability.